Life Cycle Assessment of Substitute Natural Gas production from biomass and electrolytic hydrogen. (19th October 2021) - Bargiacchi, Eleonora; Candelaresi, Daniele; Valente, Antonio; Spazzafumo, Giuseppe; Frigo, Stefano
Abstract: The synthesis of a Substitute Natural Gas (SNG) that is compatible with the gas grid composition requirements by using surplus electricity from renewable energy sources looks a favourable solution to store large quantities of electricity and to decarbonise the gas grid network while maintaining the same infrastructure. The most promising layouts for SNG production and the conditions under which SNG synthesis reduces the environmental impacts if compared to its fossil alternative is still largely untapped. In this work, six different layouts for the production of SNG and electricity from biomass and fluctuating electricity are compared from the environmental point of view by means of Life Cycle Assessment (LCA) methodology. Global Warming Potential (GWP), Cumulative Energy Demand (CED) and Acidification Potential (AP) are selected as impact indicators for this analysis. The influence of key LCA methodological aspects on the conclusions is also explored. In particular, two different functional units are chosen: 1 kg of SNG produced and 1 MJ of output energy (SNG and electricity). Furthermore, different approaches dealing with co-production of electricity are also applied. The results show that the layout based on hydrogasification has the lowest impacts on all the considered cases apart from the GWP and the CED with SNG mass as the functional unit and the avoided burden approach. Finally, the selection of the multifunctionality approach is found to have a significant influence on technology ranking. Highlights: The LCA of six production routes of a substitute of natural gas is performed. The layout involving hydrogasification shows the most favourable performance. The electrolyser infrastructure arises concerns linked to acidification footprint. Methodological aspects affect the ranking of the considered technologies.